Analisis Diversifikasi Dampak Setelah Merger dan Akuisisi Pada Kinerja Keuangan Perusahaan yang Terdaftar di BEI - Dian Fajar Suryani; Fahri Ansari Siregar; Ridha Shafina Nur; Zulfahmi Napitupulu; Suhairi Suhairi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
In the era of globalization and free trade, the act of conducting mergers and acquisitions is a decision that is increasingly used in business practices and is getting better and better to be considered together. In operating a business, business leadership is always needed to maintain optimal business growth. Executing an M&A strategy is a shortcut to business growth without having to run the business from scratch, for a new type of business. In situations where large entities usually acquire other entities in order to increase competitiveness and minimize expenses. Companies that opt ​​for mergers and acquisitions will get a larger market share and better profits. The method used in this paper is the literature review method. The literature review reviews the scientific literature on a topic and critically analyzes the impact of diversification that occurs after mergers and acquisitions on the level of financial operations of an entity listed on the Indonesia Stock Exchange. mergers and acquisitions as a way for companies to develop their business without starting a new business will certainly have an effect, From the results of the literature review conducted that mergers and acquisitions do not always give great results to the financial operations of an entity, this result could be due to the mission of an entity to merge and acquisitions are for the long ter. Keywords: Acquisition, Financial Performance, Merger